2011
DOI: 10.2147/ceg.s15373
|View full text |Cite
|
Sign up to set email alerts
|

New and emerging treatments for the prevention of recurrent diverticulitis

Abstract: Sigmoid diverticulitis is a common benign condition which carries significant morbidity and socioeconomic burden. This article describes the management of sigmoid diverticulitis with a focus on indications for surgical intervention. The mainstay of management of uncomplicated diverticulitis is broad-spectrum antibiotic therapy. The old surgical dictum that two episodes of sigmoid diverticulitis warranted surgical intervention has been challenged by recently published data. Surgery for diverticulitis thus needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In most cases, this resection may be done in the elective setting, avoiding the need for a temporary stoma. Indeed, several systemic reviews and meta-analyses [19,20,21,22,23] concluded that further investigation is needed in order to define the role of laparoscopic peritoneal lavage and drainage in the treatment of acute diverticulitis. The LADIES trial, a Dutch multicenter prospective trial [24] that compared peritoneal lavage, Hartmann procedure and resection with primary anastomosis has been prematurely terminated at interim analysis owing to high complication rates in the lavage and drainage group.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, this resection may be done in the elective setting, avoiding the need for a temporary stoma. Indeed, several systemic reviews and meta-analyses [19,20,21,22,23] concluded that further investigation is needed in order to define the role of laparoscopic peritoneal lavage and drainage in the treatment of acute diverticulitis. The LADIES trial, a Dutch multicenter prospective trial [24] that compared peritoneal lavage, Hartmann procedure and resection with primary anastomosis has been prematurely terminated at interim analysis owing to high complication rates in the lavage and drainage group.…”
Section: Discussionmentioning
confidence: 99%
“…[17, 19, 20]. As a result, some authors have argued for interval resection following an initial episode of diverticulitis in IMS patients [4, 17, 21, 22] [23]. However, these studies are limited by small sample sizes, variable types of immunosuppression, and a lack of follow-up beyond the initial hospitalization for diverticulitis.…”
Section: Introductionmentioning
confidence: 99%